Algunas relaciones entre las zonas de surgencia del Pacífico Centroamericano y los Océanos Pacífico y Atlántico Tropical - Alfaro, Eric J. (2001)
In order to explore the influence of the surrounding tropical oceans on the Central American Pacific coast, a Transfer Function Model was fixed to Sea Surface Temperature Anomalies (SSTA) of the Gulf of Tehuantepec, Papagayo, Panama and Quepos time series. As independent variables the following were used: Niño 3.4, Tropical North and South Atlantic indices. These models show that Niño 3.4 has the most important influence over the region when compared with the influence of the other indices, having positive correlation with all the SSTA series. It shows an influence of this index on the relative termocline’s depth in front of the Central American Pacific Coast.